Potato miR828 Is Associated With Purple Tuber Skin and Flesh Color - Bonar, Nicola; Liney, Michele; Zhang, Runxuan; Austin, Ceri; Dessoly, Jimmy; Davidson, Diane; Stephens, Jennifer; McDougall, Gordon; Taylor, Mark; Bryan, Glenn J.; Hornyik, Csaba (Frontiers in Plant Science, 2018)
Anthocyanins are plant pigments responsible for the colours of many flowers, fruits and storage organs and have roles in abiotic and biotic stress resistance. Anthocyanins and polyphenols are bioactive compounds in plants including potato (Solanum tuberosum L.) which is the most important non-cereal crop in the world, cultivated for its tubers rich in starch and nutrients. The genetic regulation of the flavonoid biosynthetic pathway is relatively well known leading to the formation of anthocyanins. However, our knowledge of post-transcriptional regulation of anthocyanin biosynthesis is limited. There is increasing evidence that micro RNAs (miRNAs) and other small RNAs can regulate the expression level of key factors in anthocyanin production. In this study we have found strong associations between the high levels of miR828, TAS4 D4(-) and purple/red colour of tuber skin and flesh. This was confirmed not only in different cultivars but in pigmented and non-pigmented sectors of the same tuber. Phytochemical analyses verified the levels of anthocyanins and polyphenols in different tissues. We showed that miR828 is able to direct cleavage of the RNA originating from Trans-acting siRNA gene 4 (TAS4) and initiate the production of phased small interfering RNAs (siRNAs) whose production depends on RNA-dependent RNA polymerase 6 (RDR6). MYB transcription factors were predicted as potential targets of miR828 and TAS4 D4(-) and their expression was characterized. MYB12 and R2R3-MYB genes showed decreased expression levels in purple skin and flesh in contrast with high levels of small RNAs in the same tissues. Moreover, we confirmed that R2R3-MYB and MYB-36284 are direct targets of the small RNAs. Overall, this study sheds light on the small RNA directed anthocyanin regulation in potato, which is an important member of the Solanaceae family.